An Evaluation of Biopesticide Beauveria Bassiana and PFP (Preptual Fungal Power) to Control Pomegranate Fruit Borer, Rapala Varuna: Comparative Evaluation of Biopesticides for Pomegranate Fruit Borer Control (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In order to find an alternative to chemical pesticides organophosphates, which are proven hazardous in long term use, the present study was conducted to evaluate the efficacy of some biopesticides for the management of the pomegranate fruit borer, Rapala Varuna. The biopesticides namely Beauveria Bassiana, and PFP available online for sale evaluated. Beauveria bassiana was less efficacious where the fruit infestation recorded was 30.56 per cent, while more than 90 in case of PFP respectively. The higher benefit cost ratio (BCR) was recorded in case of PFP.